Molecular Mechanisms of Chemotherapy Resistance in Head and Neck Cancers - Kanno, Yuzuka; Chen, Chang-Yu; Lee, Hsin-Lun; Chiou, Jeng-Fong; Chen, Yin-Ju (Frontiers in Oncology, 2021)
Chemotherapy resistance is a huge barrier for head and neck cancer (HNC) patients and therefore requires close attention to understand its underlay mechanisms for effective strategies. In this review, we first summarize the molecular mechanisms of chemotherapy resistance that occur during the treatment with cisplatin, 5-fluorouracil, and docetaxel/paclitaxel, including DNA/RNA damage repair, drug efflux, apoptosis inhibition, and epidermal growth factor receptor/focal adhesion kinase/nuclear factor-κB activation. Next, we describe the potential approaches to combining conventional therapies with previous cancer treatments such as immunotherapy, which may improve the treatment outcomes and prolong the survival of HNC patients. Overall, by parsing the reported molecular mechanisms of chemotherapy resistance within HNC patient’s tumors, we can improve the prediction of chemotherapeutic responsiveness, and reveal new therapeutic targets for the future.